ANALISIS DISTRIBUSI SARANG PENYU HIJAU Chelonia mydas DI PULAU JEMUR RIAU - Yustina '; Suwondo '; Arnentis '; Yuspen Hendri (Biogenesis, 2004)
A  surveys  of  three  station  along  the  nesting  beach  for  distribution  nesting  analysis  with  beach characteristics  and  microclimatic  nesting  green  turtles  Chelonia  mydas in  Pulau  Jemur-Riau  was conducted  in  April- July  2002.  The  spatial  distribution  along  the  nesting  beach  namely  the  nesting abundant at highest the beach slope are 24°-31°, the grain sizes are medium sand (MZ = 2,18) and coarse sand (MZ =1,34). Temporary distribution in the nesting begins in April, extends through May and June, and   decreases  during  July.   The  coral  stones  are  limiting  factor  for     landing  beach   success.   The characteristic   of  nesting   (beach   slope)   indicate  microclimatic  effect  on   nesting  and  impacted  for distribution  was reducing abundant of nesting.  Canopy  vegetation  at highest beach  slope are 30° had microclimatic effect on nesting.   Key words : Distribution, microclimatic, nesting, green turtles, Pulau Jemur